Habilidades Investigativas: definición del problema dentro del trabajo de integración curricular desarrollado por estudiantes de Educación Superior - Guerrero Urbano, Jessica Fernanda (2024)
The quality of an investigative work depends largely on the effective definition of the research problem. This study focuses on analyzing the influence and level of research skills among university students during the initial phase of problem definition in academic projects. The participants are students in the last semester of their degree of a public Ecuadorian university. These skills encompass seven domains: exploratory, technological, methodological, analytical and interpretative, written and oral communication, and cooperative skills. Additionally, it aims to establish an effective methodology for addressing problem definition in research based on the obtained results. A non-experimental, involving field and documentary, with a quantitative and descriptive methodological approach, and involving 364 students. The survey was used as a technique, and two questionnaires were employed: "Validated Scale of Research Skills" and "Process for Defining a Problem in a Curricular Integration Work." The first questionnaire was validated, and the second was designed. Regarding the findings, a moderately positive correlation (rho = 0.316**) between research skills and problem definition was observed, supporting the alternative hypothesis. Concerning the level of research skills in students, the cooperative domain emerged as the strongest at 86.8% (sum of "almost always" and "always"). Next is the written domain at 81.3%, followed by the technological domain at 76.7%. Oral (66.5%), methodological (66%), and exploratory (60.7%) domains rank fourth in terms of dominance. Finally, the analytical and interpretative domain is the least developed at 48%. The relevance of the scientific method for addressing proposed research problems and its adherence to presented needs is highlighted. Keywords: Higher Education, Research Skills, Research